Kombinasi Ekstrak Etanol Daun Salam (Syzygium polyanthum) dan Daun Jambu Biji (Psidium guajava L.) Sebagai Antidiabetes Oral pada Tikus Putih (Rattus novergicus) - sukmawati, sukmawati; Emelda, Andi; Astriani, Yesi Rika (Pharmaceutical Journal of Indonesia, 2018)
Diabetes mellitus is a collectionÂ  metabolic disorders which is characterized y a state of hyperglycaemia. Flavanoids in bay leaves and tannins in guava leaves have potential as an antidiabetic. This research aimed to determine the combination effects of ethanol extract of bay leaves and guava leaves as an oral antidiabetic. This research method used pre-post control group design. A total of 15 rats were divided into 5 groups. Group I (negative control) was given Na CMC 1%, group II (positive control) was given acarbose 1,02 mg/kgBW, group III was given EEDS 31,25 mg/kgBW: EEDJB 50 mg/kgBW, group Â IV was given EEDS 31,25 mg/kgBW: EEDJB 100 mg/kgBW, and group V was given EEDS 62,5 mg/kgBW: EEDJB 50 mg/kgBW. The rats previously induced by alloxan 135 mg/kgBW intraperitoneally. Data analysis used one way Anova and followed by bonferroni test to find out the significant difference between the treatments. The results of study showed that the combination EDS 31,25 mg/kgBW: EEDJB 100 mg/kgBW, EEDS 62,5 mg/kgBW: EEDJB 50 mg/kgBW, and EEDS 31,25 mg/kgBW: EEDJB 50 mg/kgBW can lower the blood glucose content of the rats which were induced by alloxan.